"Det vi har bruk for, står aldri i bøkene" - Vaalund, Ingrid J. (Nordiske Studier i Leksikografi, 1997)
In this article I describe some of the problems I encounter in my work as a television subtitler - like having to create believeable Norwegian translations for terms in nonexistent universes.